Efficacy of Hyoscine Butylbromide Versus Drotaverine in Relieving Acute Nonspecific Abdominal Pain in Children- A Non - Randomized Trial - Kumar Paudel, Pradip; Basnet, Sudha; Shreshtha, Merina (Journal of Nepal Paediatric Society, 2022)
Introduction: Acute abdominal pain is a very common complaint for children presenting to the emergency department (ED). The purpose of this study was to compare efficacy of hyoscine and drotaverine for relieving acute nonspecific abdominal pain in children presenting to ED. Methods: Total of 52 children aged six years to 16 years were enrolled in a non-randomized trial at Paediatric ED of TUTH from Dec 2017 to June 2018, and randomly allocated to drotaverine or hyoscine groups; 26 in each group. Face pain score-revised tool was used to measure the efficacy of the drug. The primary outcome was to measure the reduction of face pain score (Self-reported) by at least 2 / 10 at 60 minutes after ingestion of study intervention. Other outcomes were requirement of rescue analgesia and adverse effects of drugs. Results: A total of 20 (77%) in hyoscine and 21 (81%) in drotaverine group responded to oral medication at the end of 60 minutes of oral administration and the difference was not statistically significant (p=0.808). Vomiting was only adverse event present in five (19%) in drotaverine and two (8%) in hyoscine groups, respectively. Conclusions: In this single center randomized controlled trial, both hyoscine and drotaverine were found to be equally efficacious for relieving acute non-specific abdominal pain in children.